2024
DOI: 10.3390/tropicalmed9020038
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Prevalence and Subtypes Distribution of Blastocystis spp. in Humans of Latin America: A Systematic Review

Carmine Fusaro,
Jaime E. Bernal,
Rosa Baldiris-Ávila
et al.

Abstract: Blastocystis spp. are among the few enteric parasites with a prevalence that can reach up to approximately 80% in communities of developing countries. This systematic review updates and summarizes available literature on the molecular prevalence and subtype distribution of Blastocystis spp. in Latin American people. This work follows the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The literature revised covers from 1 January 2015 to 6 October 2023 in seven different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 111 publications
1
0
0
Order By: Relevance
“…The genus Blastocystis comprises a variety of lineages, called STs, and more than 90% of human isolates are grouped into STs 1-4 [39]. The distribution of STs in our samples demonstrated that ST3 was the most frequently detected ST, followed by ST2 and ST1, as other studies have reported [20,40,41]. Several authors have reported gastrointestinal symptoms associated with ST3 [42][43][44], and more specifically, the possible pathogenic association of allele 34, the most common in our study (57.9%; 11/19) with urticaria [39,42].…”
Section: Discussionsupporting
confidence: 67%
“…The genus Blastocystis comprises a variety of lineages, called STs, and more than 90% of human isolates are grouped into STs 1-4 [39]. The distribution of STs in our samples demonstrated that ST3 was the most frequently detected ST, followed by ST2 and ST1, as other studies have reported [20,40,41]. Several authors have reported gastrointestinal symptoms associated with ST3 [42][43][44], and more specifically, the possible pathogenic association of allele 34, the most common in our study (57.9%; 11/19) with urticaria [39,42].…”
Section: Discussionsupporting
confidence: 67%